2022
DOI: 10.1007/s12020-022-03186-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TSH suppressive therapy on bone mineral density (BMD) and bone turnover markers (BTMs) in patients with differentiated thyroid cancer in Northeast China: a prospective controlled cohort study

Abstract: This study aimed to evaluate the effects of thyroid-stimulating hormone (TSH) suppressive therapy on bone mineral density (BMD) and bone turnover markers (BTMs) in differentiated thyroid cancer (DTC) patients after postoperative 1-2 years in Northeast China. MethodsFive male, sixteen premenopausal, and eight postmenopausal female DTC patients receiving TSH suppressive therapy after thyroidectomy were enrolled. Patients were matched with healthy controls in a ratio of 1:2. All participants completed postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In contrast, TBS scores were significantly decreased in this period. This is in agreement with previous reports, that a significative BMD loss is only found after a long disease duration [12]. Also, bone microarchitecture was found to diminish more in patients who had incidental VFs during this long period.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, TBS scores were significantly decreased in this period. This is in agreement with previous reports, that a significative BMD loss is only found after a long disease duration [12]. Also, bone microarchitecture was found to diminish more in patients who had incidental VFs during this long period.…”
Section: Discussionsupporting
confidence: 93%
“…This result also correlates with a study from Gürlek et al, who evaluated 15 premenopausal women with endogenous subclinical hyperthyroidism for between six and 11 months, and who did not show reduced BMD 36 . A more recent study from Wang et al observed 29 DTC patients 1–2 years postoperatively in whom there was no significant effect on BMD 32 . Most likely, these outcomes are related to the short time window between the two measurements.…”
Section: Discussionmentioning
confidence: 95%
“…On the one hand, some studies indicate that suppressed TSH levels cause lower BMD 29 31 . On the other hand, various studies demonstrate the opposite and report that there is no significant difference regarding BMD in those patients 32 35 . Primarily due to these controversies and because of the clinical importance, we decided to examine bone densities in two age- and sex-matched cohorts with significantly different TSH values over a long period of time.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is similar to the cooling principle of an air conditioner. The refrigerant changes between gaseous, liquid, high-pressure, or low-pressure 33 . From the outside, the refrigerant passes through the compressor, condenser, expansion valve, and evaporator, constantly releasing or absorbing heat.…”
Section: Theoretical Basis and Methods Construction Researchmentioning
confidence: 99%